2019
DOI: 10.3389/fnins.2019.01129
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Enhancement by Transcranial Photobiomodulation Is Associated With Cerebrovascular Oxygenation of the Prefrontal Cortex

Abstract: Transcranial infrared laser stimulation (TILS) is a novel, safe, non-invasive method of brain photobiomodulation. Laser stimulation of the human prefrontal cortex causes cognitive enhancement. To investigate the hemodynamic effects in prefrontal cortex by which this cognitive enhancement occurs, we used functional near-infrared spectroscopy (fNIRS), which is a safe, non-invasive method of monitoring hemodynamics. We measured concentration changes in oxygenated and deoxygenated hemoglobin, total hemoglobin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…The reliability of our bbNIRS method was first shown by Wang et al, 2017 [8] and then by the replication study of Pruitt et al, 2020 [6] in young and elderly participants. We have also shown the hemodynamic increases in [HbO] after TILS during two cognitive tasks (psychomotor vigilance task and delayed match to sample task) in Holmes et al, 2019 [5]. Kolyva et al, 2012 [37] have also previously shown increase on D…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The reliability of our bbNIRS method was first shown by Wang et al, 2017 [8] and then by the replication study of Pruitt et al, 2020 [6] in young and elderly participants. We have also shown the hemodynamic increases in [HbO] after TILS during two cognitive tasks (psychomotor vigilance task and delayed match to sample task) in Holmes et al, 2019 [5]. Kolyva et al, 2012 [37] have also previously shown increase on D…”
Section: Discussionsupporting
confidence: 60%
“…Since neurons are critically dependent on oxygen metabolism, TILS actions on CCO and hemoglobin oxygenation lead to multiple beneficial effects [3,10]. These effects include more efficient oxygen consumption for bioenergetics [2,3], resulting in enhanced PFC-based cognitive functions such as attention and working memory [5,11,12], executive function [13], and rule-based category learning [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…fNIRS is an inexpensive, relatively portable, and tolerant of motion artifacts neuroimaging method compare with other measurements which is completely noninvasive and could be used in daily life [ 22 , 30 ]. The fNIRS is widely employed to investigate human cognition [ 31 33 ]. The frontal areas of the brain, specifically the prefrontal cortex (PFC), are associated with cognition [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%